Manure Efeects And Lime Against Diameter and Production Rhizome Red Ginger (Zingiber officinale var. Amarum) : Efek Pupuk Kandang Dan Kapur Terhadap Diameter Dan Produksi Rimpang Jahe Merah (Zingiber officinale var. Amarum) - Akhmad Sopian (Universitas Widya Gama Mahakam, 2013)
This study aims to examine the role of goat manure and lime Dolomite and their interaction on the growth and yield of red ginger (Zingiber officinale var Amarum). Research has been conducted in February 2011 to July 2011 in farmers' fields in the village of White Water District of Samarinda Ulu. The experimental design used randomized block design (RBD) with factorial pattern, consisting of two factors; The first factor goat manure (k) which comprises 4 levels doses (k0 = control without manure, k1 = 1.3 kg / m2, k2 = 1.8 kg / m2, k3 = 2.4 kg / m2) and the second factor is the provision of dolomite (d) which consists of 4 levels doses, (d1 = 100 g / m2, d2 = 200gr / m2, d3 = 300 g / m2, d4 = 400 g / m2) and each treatment combination repeated 3 times. The results showed no significant effect on the provision of goat manure and dolomite lime to red ginger plant growth, but the real impact on the fresh rhizome weight per plot (kg), fresh rhizome weight per plant (kg) and fresh rhizome production (tonnes / ha ). Effect of manure and dolomite are the best on the growth and production of red ginger plant is achieved by treatment k2 = 1.8 kg / m2 and d4 = 400 g / m2).